Effect of physicochemical factors and use of milk powder on milk rennet-coagulation: Process understanding by near infrared spectroscopy and chemometrics. (January 2021) - Strani, Lorenzo; Grassi, Silvia; Alamprese, Cristina; Casiraghi, Ernestina; Ghiglietti, Roberta; Locci, Francesco; Pricca, Nicolò; De Juan, Anna
Abstract: The effect of physicochemical factors and use of skim milk powder on milk rennet-coagulation was investigated combining near infrared (NIR) spectroscopic monitoring and Multivariate Curve Resolution - Alternating Least Squares (MCR-ALS). Coagulum formation has been studied by reference approaches (Formagraph and fundamental rheology) and with NIR spectroscopy on unaltered reconstituted milk samples, pasteurized samples, samples with calcium chloride addition and samples of reconstituted milk mixed with fresh milk. The MCR-ALS models successfully described the process evolution, explaining more than 99.9% of variance. The MCR-ALS profiles revealed to be significantly directly correlated with Formagraph and rheological data (p < 0.001) and allowed assessing the significant effect (p < 0.05) of the milk powder type on the coagulation occurrence and the non-significance (p > 0.05) of the CaCl2 concentration level added and the heat treatment applied. The MCR-ALS models calculated for the coagulation trials of pasteurized skimmed milk mixed with reconstituted milk samples highlighted shorter coagulation times with the increasing of reconstituted milk amount (from 4.3-6.6 min to 2–5 min). Profiles extracted from MCR-ALS models developed for a wide range of coagulation conditions proved to be suitable non-destructive, non-invasive and on-line tools to evaluate the rennet-induced coagulation of reconstituted milks. Highlights: Assessment of milk powder type, CaCl2 and heat treatment effects on coagulation. Different ratios of milk and reconstituted milk powder affect coagulation. FT-NIR spectroscopy coupled with MCR-ALS successfully monitors milk coagulation. Good correlation between FT-NIR spectroscopy, rheology and Formagraph. The proposed method is suitable for an on-line application to control coagulation.